How do the effects of toxicity in competitive online video games vary by source and match outcome? - Jacob Morrier; Amine Mahmassani; R. Michael Alvarez (PLoS ONE, 2025)
This article seeks to estimate variations in the effects of toxicity in competitive online video games by source and match outcome. To this end, we analyze proprietary data from the first-person action video game Call of Duty®: Modern Warfare® III, published by Activision®. To overcome causal identification issues, we implement an instrumental variable estimation strategy. Our findings confirm that exposure to toxicity has statistically significant causal effects on short-term player engagement and the probability that players engage in similar behavior in the current match. Further, we show that these effects vary significantly depending on whether toxicity originates from opponents or teammates, whether it originates from teammates in the same or a different party, and the match’s outcome. These findings have meaningful implications regarding the allocation of resources for combating toxicity and the nature of toxicity across various contexts.